2005
DOI: 10.1001/archinte.165.10.1167
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cyanocobalamin Supplementation in Older People With Vitamin B12 Deficiency

Abstract: The lowest dose of oral cyanocobalamin required to normalize mild vitamin B(12) deficiency is more than 200 times greater than the recommended dietary allowance, which is approximately 3 mug daily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(129 citation statements)
references
References 22 publications
7
120
1
1
Order By: Relevance
“…Animal studies in mice and rats have already revealed that modulating Hcy levels by means of methionine-enriched diets caused an increase in bone resorption [34,35], indicating that nutrient intervention can modulate bone resorption via alteration of Hcy levels. In the elderly, Hcy levels can effectively be reduced by means of B 12 and folate supplementation [36][37][38]. The novel observation that MMA is also able to induce osteoclast formation indicates that not only Hcy but also MMA levels need to be attenuated in order to prevent osteoporosis via nutrient supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies in mice and rats have already revealed that modulating Hcy levels by means of methionine-enriched diets caused an increase in bone resorption [34,35], indicating that nutrient intervention can modulate bone resorption via alteration of Hcy levels. In the elderly, Hcy levels can effectively be reduced by means of B 12 and folate supplementation [36][37][38]. The novel observation that MMA is also able to induce osteoclast formation indicates that not only Hcy but also MMA levels need to be attenuated in order to prevent osteoporosis via nutrient supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…The novel observation that MMA is also able to induce osteoclast formation indicates that not only Hcy but also MMA levels need to be attenuated in order to prevent osteoporosis via nutrient supplementation. It has previously been shown that B 12 supplementation leads to a reduction in plasma MMA levels in elderly with B 12 deficiency [36,39]. To date, studies on the effect of B 12 and/or folate supplementation on bone health are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies in healthy populations and in patients have investigated the effect of various doses of folic acid supplementation in lowering tHcy, few have examined the independent effects of vitamin B 12 . In those studies that have administered low-dose vitamin B 12 as a separate treatment, the response of vitamin B 12 biomarkers was the primary outcome and the tHcy response was measured as a secondary objective (21,22) . Furthermore, the study populations were selected for mild vitamin B 12 deficiency and were not pretreated with folic acid before vitamin B 12 supplementation.…”
Section: Vitamin B 12mentioning
confidence: 99%
“…Plasma homocysteine concentrations are influenced by a complex interaction of environmental and genetic factors, such as nutrition, lifestyle, renal function and hormonal factors. Elevated levels can be reduced by vitamin B6, B12 or folic acid supplementation, which are essential co-factors in the homocysteine metabolism (van Oort et al, 2003;Eussen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%